Enzyme immunoassay detection of platelet-derived microparticles and RANTES in acute coronary syndrome - Nomura, Shosaku; Uehata, Shigeru; Saito, Sonoko; Osumi, Kazuoki; Ozeki, Yasushi; Kimura, Yukio (Thrombosis and Haemostasis, 2003)
Platelet-derived microparticles (PDMPs) are produced by platelet activation or physical stimulation under various conditions. To evaluate changes in platelet and chemokine function in patients undergoing percutaneous transluminal coronary angioplasty (PTCA), we measured and compared levels of PDMPs and a C-C chemokine, regulated on activation normally T-cell express and secreted (RANTES), by ELISA. Levels of PDMP and RANTES in patients with acute coronary syndrome were significantly higher than those in the control groups (PDMP: 20.1 ± 2.9 vs 80.4 ± 7.3 U/ml, p < 0.001; RANTES: 18.6 ± 3.7 vs 52.1 ± 4.6 ng/ml, p < 0.01), but did not differ between the control groups and patients with stable angina. PDMP levels were higher in patients with acute myocardial infarction (AMI) than in patients with unstable angina (PDMP:115.0 ± 7.1 vs 63.9 ± 6.2 U/ml, p < 0.001). There was no difference in the RANTES levels, however, between patients with AMI and patients with unstable angina. PDMP and RANTES levels were significantly decreased after PTCA (PDMP, p < 0.001; RANTES, p < 0.05), but without differences between the two groups. In addition, the level of PDMP was significantly correlated with that of RANTES or soluble CD40 ligand. These findings suggest that PTCA may prevent the development of AMI-associated complications in which activated platelets and RANTES play roles. Our ELISA method appears to be sufficient for monitoring PDMP and RANTES levels after PTCA in patients with acute coronary syndrome.
Keywords: Platelet-derived microparticle; acute coronary syndrome; RANTES; ELISA; PTCA